Scheme of obtaining ß-carotene standard from pumpkin (Cucurbita moschata) flesh - Shahidan, Norshazila; Othman, Rashidi; Jaswir, Irwandi; Hashim, Yumi Zuhanis Has-Yun (2011)

(untitled)
Characterization and quantification of carotenoids composition is complicated, costly and time-consuming. The accuracy and the reliability of the data depend solely on the standards and HPLC but a major constraint is acquiring and maintaining pure standards. Carotenoid standards are commercially available but they are expensive and are prone to isomerization and oxidation. Thus the purpose of this study is to establish analytical method for isolating beta-carotene by open column chromatography from pumpkin or Cucurbita moschata to be used as one of the carotenoid standards for determination of total and individual carotenoids. Pumpkin with orange flesh has been chosen due to the non-seasonal and abundance all year round. The study on the scheme of obtaining beta-carotene standard from pumpkin flesh demonstrated that the purity of beta-carotene standard evaluated by HPLC was 97.95%. The standard curves with five different concentrations for betacarotene in triplicate were constructed by plotting the area against the concentration. The coefficient of correlation was 0.9990. This study established that pumpkin can be a reliable source of beta-carotene standard which is cheap and can provide a constant supply throughout the year.